About the marginal novel spaces in Adolfo Couve’s La comedia del arte (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
The present work seeks to reflect, from the perspective of interartistic studies, on the narrative practice of Adolfo Couve, Chilean writer and painter who thematizes the plastic world in all his narrative production. Starting from an unprejudiced conception regarding the marginal, the ugliness and the misery, our author displays an alternate look on the edge spaces in search of the vindication of the misery, at the same time that relativizes the aesthetic canon that prestige subjects and reasons far from the reference field of those who inhabit the edge. The exhibition of those spaces, the characters and the minority landscapes, their plastic and narrative composition, nevertheless, permanently dialogue with the pictorial tradition of elite.
Keywords: Adolfo Couve; space; visual arts; exhibition; residential; circus